Sistem Informasi Pendidikan Madrasah atau Pesantren - Roro Fatikhin; Nuari Anisa Sivi; Nurhidayah Nurhidayah (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
Madrasas and Islamic boarding schools are Islamic educational institutions that have a strategic role in shaping the character, morals, and competencies of students. In addition to carrying out the formal learning process, these two institutions are also centers for moral, spiritual, and social development. In their operations, madrasas and pesantren manage various administrative activities, such as student data collection, attendance recording, grade processing, teacher data management, lesson schedule preparation, and delivery of academic information to related parties. However, many institutions still use manual systems that rely on notebooks or separate applications that are not integrated. This condition poses a number of obstacles, including the high risk of recording errors, duplicate data that is difficult to track, the slow process of recapitulation of grades and attendance, and delays in the delivery of academic information. In addition, manual processes cause administrative management to be less efficient and prone to data loss. As the need for fast, accurate, and accurate information increases, technological solutions are needed that are able to integrate all administrative and academic processes in one centralized system. Web-based information systems are an effective alternative to improve work efficiency, minimize errors, and facilitate access to information for teachers, students, and guardians. With the implementation of a well-managed system, madrasas and Islamic boarding schools are expected to improve the quality of services and support a more modern, structured, and sustainable learning process.